Corporate Governance Country Assessment : Kenya - World Bank (Washington, DC, 2014)
Good corporate governance ensures that companies use their resources more efficiently, protects minority shareholders, leads to better decision making, and improves relations with workers, creditors, and other stakeholders. It is an important prerequisite for attracting the patient capital needed for sustained long-term economic growth. This report provides an assessment of Kenya s corporate governance policy framework. It highlights recent improvements in corporate governance regulation, makes policy recommendations, and provides investors with a benchmark against which to measure corporate governance in Kenya.